Effects of human milk fortifier with iron on the bacteriostatic properties of breast milk - Leticia Fuganti Campos (Jornal de Pediatria (Versão em Português), 2013)
Objective: To compare bacterial growth in pure colostrum versus colostrum with human milk fortifier (HMF) containing iron. Methods: The growth of Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa in 78 samples of pure colostrum or colostrum with added iron-containing HMF was compared. For qualitative analysis, filter paper discs were immersed in samples from each group and incubated for 48 hours with 101 colony forming units (CFUs)/mL of each strain. For quantitative assessment, 1 mL of each strain containing 107 CFUs/mL was homogenized with 1 mL of either colostrum or colostrum with human milk fortifier, seeded into a Petri dish, and incubated at 37 °C. Twenty-four hours later, the number of CFUs was counted. Results: The qualitative analysis showed no difference in bacterial growth. In the quantitative evaluation, E. coli growth in the control group was 29.4±9.7 × 106 CFU/mL, while in the HMF group it was 31.2±10.8 × 106 CFU/mL. The difference between the average growth was 1.9±4.9 × 106 CFU/mL (p = 0.001). There were no differences in S. aureus and P. aeruginosa growth. Conclusion: Addition of iron at this concentration reduces breast milk bacteriostatic action against E. coli.